ANALISIS FLEKSIBILITAS SUPPLY CHAIN BERBASIS MAKE TO ORDER DENGAN METODE FUZZY-AHP PADA KONVEKSI UD HASBY PONOROGO - Nindar Septiani Eka Pratiwi; Wiwik Handayani (STKIP Persada Khatulistiwa Sintang, 2022)
The convection industry sector in Indonesia is still experiencing a slump due to the pandemic. With uncertain conditions like today, demand fluctuates and changes in conditions from companies affected by the pandemic. Fluctuating demand and changing company conditions make companies must be able to balance to remain competitive. One of the determinants of a company's ability to survive or not is customer satisfaction. This study aims to determine the analysis of flexibility measurement in the supply chain system at UD Hasby Ponorogo. This study uses a quantitative descriptive approach. Data was collected through direct observation, distributing questionnaires, and literature studies. The methods used in this research are Fuzzy-AHP (Analytical Hierarchy Process) and OMAX (Objective Matrix) methods. The results of the analysis found that the level of supply chain flexibility in the company UD Hasby Ponorogo as a whole is flexible (enough), where all the main dimensions reach a percentage between 60-80%. However, it needs to be improved so that the flexibility can be maximized